Peningkatan Disiplin Kerja Karyawan melalui Edukasi Internal - Endang Silaningsih; Siti Aidini Khoerunnisa (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Employee work discipline is one of the important aspects of human resource management, especially in service companies that heavily rely on their employees' performance. PT CAI, as an event organizer company, still faces issues related to employee work discipline, such as tardiness, absenteeism without notice, and low consistency in completing work responsibilities. This activity is a form of Community Service by students aimed at increasing employees' understanding and awareness of the importance of work discipline through educational and practical approaches. The implementation methods of the activity include observation, interviews, discussions, documentation, and the implementation of an educational program in the form of work discipline posters as well as providing recommendations for a simple reward and punishment system. The results of the activity show that internal educational media serve as an effective visual reminder in increasing employee awareness of punctuality and work responsibility. This community service activity is expected to support the improvement of employee performance, service quality, and the operational sustainability of PT CAI.